La poesia di Mallarmé e la ricerca “en hypothèse” dell’Assoluto - Gambelli, Delia (Status Quaestionis, 2016)
The essay proposes a reading of Stephane Mallarmé poetry, focusing, in particular, on some of the most “obscure” poems, i.e. “Une dentelle s’abolit”, “Ses purs ongles très haut”, and “Un coup de dés jamais n’abolira le hasard ”. To Mallarmé, ambiguity is an essential feature of poetic practice and responds to a specific poetic agenda: while rejecting intelligible language, Mallarmé strives to redress the “défaut des langues” – that is, the arbitrariness of the linguistic sign – by recovering the connections between signifier and signified, thus emancipating poetry from chance (le Hasard). “Un coup de dés…” thus exemplifies Mallarmé’s method which dignifies the written page so that it reaches the status of “ciel étoilé”, a sort of non-Euclidean geometry displaying a potentially infinite series of numbers and semantic variations.